Illuminating the impact-parameter dependence of UPC dijet photoproduction - Eskola Kari J.; Guzey Vadim; Helenius Ilkka; Paakkinen Petja; Paukkunen Hannu (EPJ Web of Conferences, 2024)
We present new NLO pQCD predictions for photoproduction of dijets in ultraperipheral PbPb collisions at 5.02 TeV with a realistic photon flux and up-to-date nuclear PDFs. Our calculation of the impact parameter dependence of the photon flux includes the effects of the nuclear form factor in the photon-emitting nucleus and the spatial dependence of nuclear PDFs of the target nucleus, which are estimated using theWood-Saxon nuclear density profile. We show that a significant portion of the measured dijets at large zγ originate from events with impact parameters of the order of a few nuclear radii, and that the cross section predictions therefore become sensitive to the modelling of the nuclear geometry and photon flux close to the source nucleus.